Desloratadine, a Novel Antigrowth Reagent for Bladder Cancer. (13th May 2020) - Ma, Jianfeng; Qi, Jinchun; Li, Shoubin; Zhang, Chaohua; Wang, Haijiang; Shao, Lijun; Yuan, Xiaofei; Sha, Quan
Desloratadine, a potent antagonist for human histamine H1 receptor, has been revealed to exhibit antihistaminic activity and anti-inflammatory activity. However, it is not yet known whether desloratadine has any effect on the biological behaviors of tumor cells. In this study, we aimed to investigate the effects of desloratadine on cell growth and invasion in bladder cancer EJ and SW780 cells in vitro . We observed that desloratadine inhibited cell viability of EJ and SW780 cells in a dose- and time-dependent manner. Desloratadine treatment was also revealed to suppress colony-formation ability and induce cell cycle arrest at G1 phase in EJ cells. Desloratadine promoted cell apoptosis via modulating the expression of Bcl-2, Bax, cleaved caspase 3, and cleaved caspase 9 in EJ and SW780 cells. Western blot resulted showed that desloratadine also impaired the expression of autophagy-related proteins, such as Beclin 1, P62, and LC3I/II in EJ and SW780 cells; while autophagy inhibitor LY294002 reversed the effects of desloratadine on these proteins. Moreover, desloratadine remarkably attenuated cell migration and invasion. Furthermore, we illustrated that desloratadine downregulated the expression of N-cadherin, Vimentin, Snail1, and Snail2, while upregulated the expression of E-cadherin in EJ and SW780 cells in vitro . The level of interleukin 6 was reduced in desloratadine-treated cells, while upregulation of interleukin 6 significantly abolished the anticancer activity of desloratadine in cell invasion and Bcl-2, Bax, Beclin1, LC3-I/II, N-cadherin, and E-cadherin expression in EJ cells. Taken together, our data suggest a potential anticancer activity of desloratadine on cell growth and invasion for bladder cancer, which may be mediated by diminishing the epithelial-to-mesenchymal transition and interleukin 6.